NEW APPROACH IN DESIGNING ENERGY-EFFICIENT TIMBER-GLASS BUILDINGS - Miroslav Premrov; Vesna Žegarac Leskovar; Boštjan Ber; Andrej Štrukelj (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
This paper offers a new approach in designing energy efficient prefabricated timber buildings using a strong interlink between an architectural and structural approach. Using building materials with quite different material properties in a way to optimally consider all of their possible advantages applied in a hybrid structural composition could be a relatively new approach in designing high-quality energy-efficient buildings. Therefore, timber and glass could be an attractive design solution in developing architectural highly attractive residential buildings. The first step in the design process of such buildings should be considered through an effective architectural approach respecting rational passive design strategies towards exploitation of maximal possible solar radiation through the glazing by the development of an optimal position and size of glass elements on the building envelope. Consequently, such an attractive building form with the non-symmetric position of timber-glass wall elements usually results in many structural problems, which can be somehow avoided if glass panes are considered as load-bearing structural elements. As a final result of the presented study loadbearing timber-glass wall, structural elements with three-layered insulating glazing were developed in a sense to increase the total racking resistance of such constructed timber-glass buildings.